2022
DOI: 10.3389/fcell.2022.955658
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish models of inflammation in hematopoietic development and disease

Abstract: Zebrafish offer an excellent tool for studying the vertebrate hematopoietic system thanks to a highly conserved and rapidly developing hematopoietic program, genetic amenability, optical transparency, and experimental accessibility. Zebrafish studies have contributed to our understanding of hematopoiesis, a complex process regulated by signaling cues, inflammation being crucial among them. Hematopoietic stem cells (HSCs) are multipotent cells producing all the functional blood cells, including immune cells. HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…MF is enriched during oxidoreductase activity and ferroxidase activity as well as when metal ions are oxidized and electrons are accepted by oxygen. Some studies have demonstrated the driving role of JAK-STAT signaling in the ability of cancer stem cells [ 19 , 20 ]. At the same time, some studies have indicated that the immune microenvironment, such as T cell activation, can be regulated via JAK/STAT molecular pathway, thereby regulating stem cell growth [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…MF is enriched during oxidoreductase activity and ferroxidase activity as well as when metal ions are oxidized and electrons are accepted by oxygen. Some studies have demonstrated the driving role of JAK-STAT signaling in the ability of cancer stem cells [ 19 , 20 ]. At the same time, some studies have indicated that the immune microenvironment, such as T cell activation, can be regulated via JAK/STAT molecular pathway, thereby regulating stem cell growth [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ontogeny of the hematopoietic system relies on a specific sequence of events and spatial and temporal cellular interactions throughout development, which control stem cell properties and balance self-renewal, quiescence, and lineage commitment [99,100]. As such, hematopoiesis is a complex and accurate developmental process that provides a good platform to identify the genetic requirements of specific critical stages and characterize the molecular mechanisms and cellular mediators of developmental inflammation [101][102][103].…”
Section: Inflammation As a Developmental Mechanism For Hspc Emergencementioning
confidence: 99%
“…Zebrafish are at the forefront of vertebrate model systems for studying vertebrate developmental hematopoiesis. The high homology of cellular components, core regulators of hematopoiesis, and conserved expression and function of genes for both myeloid/lymphoid fate determination and terminal differentiation between humans and zebrafish make them a powerful model for studying the developmental process of hematopoiesis [101,[106][107][108][109][110]. Moreover, defects in zebrafish hematopoiesis reliably phenocopy human blood disorders, including leukemia, making them an attractive model for defining critical regulators of these blood disorders [111,112].…”
Section: Zebrafish Hematopoiesismentioning
confidence: 99%
See 2 more Smart Citations